Foreign Direct Investment in Indonesia: An Analysis from Investors Perspective - Manuel Fernandez; Mariam Mohamed Almaazmi; Robinson Joseph (International Journal of Economics and Financial Issues, 2020)
Globalization has made worldwide mobility of money extremely easy. The investors prefer to invest in places that offer attractive returns and are relatively less risky. The inflow of foreign direct investment (FDI) gives developing countries access to capital that would otherwise be not available. FDI also provides much needed foreign exchange and therefore helps to adjust some of the macroeconomic imbalances in developing countries. Every country is trying to attract investors by providing business friendly environment, which are quite attractive and easy to start and generate profits. The main objectives of this study are to find out the status of Indonesia as a destination for FDI; the factors that attract FDI into Indonesia and how these can be enhanced, and the factors that hinder the flow of FDI into Indonesia and how these can be reduced.  The study covers a period of five years from 2014-2015 to 2018-2019.  The study analysis various determinants of FDI like market size, economic growth, infrastructure, political risk, corruption, labor market, raw materials, technological readiness, innovation, financial system, taxation, cost of capital, ease of doing business and government policies. The study shows that Indonesian environment is investor-friendly and has the potential to grow.